Topology to geometry in protein folding: β-Lactoglobulin - Fernandez, Ariel (2000)
Evolution of protein structure from random coil to native is first represented topologically by its time-dependent sequences of discretized Ramachandran basins occupied by successive backbone residues. Introducing energetic and entropic criteria at each instant of observation transforms the description from a structurally ambiguous topological representation to an unambiguous geometric picture of the folding process. The method is applied with success to folding of β-lactoglobulin, traditionally perplexing because of its reputed nonhierarchical folding pattern. This molecule passes through a stage, ca. 0.1 μs duration, of transient, "flickering" α-helical structure, until a bit of tertiary structure forms that stabilizes the system long enough to allow it to pass to its native β-sheet.